Chamomile (Matricaria recutita) May Have Antidepressant Activity in Anxious Depressed Humans - An Exploratory Study - Amsterdam, Jay D. (2012)
OBJECTIVE: As part of a randomized, double-blind, placebo-controlled study, we examined the antidepressant action of oral chamomile (Matricaria recutita) extract in subjects with co-morbid anxiety and depression symptoms. We hypothesized that chamomile may demonstrate a clinically meaningful antidepressant activity versus placebo. METHODS: 57 subjects received either chamomile extract or placebo therapy. Nineteen subjects had anxiety with co-morbid depression, 16 had anxiety with past history of depression, and 22 had anxiety with no current or past depression. Generalized estimating equations analysis was used to identify clinically meaningful changes over time in Hamilton Depression Rating (HAM-D) rating outcome measures among treatment groups. RESULTS: We observed a significantly greater reduction in mean total HAM-D scores (p<0.05) and HAM-D core depression item score (p<0.05) for chamomile versus placebo in all subjects, and a non-significant trend for a greater reduction in HAM-D core depression score for chamomile versus placebo in subjects with anxiety with current co-morbid depression (p=0.062). CONCLUSION: Chamomile may have clinically meaningful antidepressant activity that occurs in addition to its previously observed anxiolytic activity.